Geopolitics of Gili Trawangan: Identity, Boundaries, and Access to Resources and Modernisation - Rachman, Muhammad Fauzi Abdul; Yani, Yanyan Mochamad (Andalas Journal of International Studies (AJIS), 2022)
The use of Gili Trawangan, a small island located northwest of Lombok, has changed from a place where fishers from Sulawesi anchored their boats to become a tourist spot visited by tourists from various regions and countries, particularly for SCUBA diving. From a geopolitical point of view, the fishermen, who were the first settlers of the island, now lose their control of the territory and find it difficult to access resources, culture and economy. Investors from outside the island and abroad have controlled this island geopolitically and create their own geopolitical identity. They use Western identities and cultures to dominate geopolitics in the strategic area on the island as the market wants. These are findings derived from a six-month field study on Gili Trawangan and direct interviews with early settlers and community leaders. Finally, the primary data was analysed using the geopolitical concepts of borders and identities.